Nilai Pendidikan Karakter dalam Jejak Andi Maruddani Karaengta Bonto-Bonto - Nur Maulindah Umar; Andi Agussalim; Aswati Asri (INSIGHT: Indonesian Journal Social Studies and Humanities, 2022)
Abstract.  This study aims to describe the values of character education in the saga "Jejak Andi Maruddani Karaengta Bonto-Bonto". This type of research is descriptive qualitative research. This research was conducted by reading and taking notes with the research instrument which became the key instrument was the researcher himself, the values of character education in the saga "Traces of Andi Maruddani Karaengta Bonto-Bonto" This research was obtained from a book adapted by Samsu Alam Nyonri and H. M. Talibau B. With the title "Traces of Andi Maruddani Karaengta Bonto-Bonto". The results of this study found twelve character education values contained in the saga "Jejak Andi Maruddani Karaengta Bonto-Bonto" namely: (1) religious, (2) tolerance, (3) hard work, (4) creative, (5) democracy, (6) curiosity (7) national spirit, (8) love of the motherland, (9) communicative (10) appreciating achievement, (11) caring for sausages, (12) responsibility. based on the research that has been done it can be concluded that in In the saga of Andi Maruddani Karaengta Bonto-Bonto's footsteps, there is a value for character education.Keywords: the value of character education, Traces of Andi Maruddani Karaengta Bonto-Bonto.